Pregabalin reduces cocaine self‐administration and relapse to cocaine seeking in the rat. (27th June 2012) - de, Giordano; Cippitelli, Andrea; Somaini, Lorenzo; Gerra, Gilberto; Li, Hongwu; Stopponi, Serena; Ubaldi, Massimo; Kallupi, Marsida; Ciccocioppo, Roberto
Abstract Pregabalin (Lyrica™) is a structural analog of γ‐aminobutyric acid (GABA) and is approved by the FDA for partial epilepsy, neuropathic pain and generalized anxiety disorders. Pregabalin also reduces excitatory neurotransmitter release and post‐synaptic excitability. Recently, we demonstrated that pregabalin reduced alcohol intake and prevented relapse to the alcohol seeking elicited by stress or environmental stimuli associated with alcohol availability. Here, we sought to extend these findings by examining the effect of pregabalin on cocaine self‐administration (0.25 mg/infusion) and on cocaine seeking elicited by both conditioned stimuli and stress, as generated by administration of yohimbine (1.25 mg/kg). The results showed that oral administration of pregabalin (0, 10 or 30 mg/kg) reduced self‐administration of cocaine over an extended period (6 hours), whereas it did not modify self‐administration of food. In cocaine reinstatement studies, pregabalin (10 and 30 mg/kg) abolished the cocaine seeking elicited by both the pharmacological stressor yohimbine and the cues predictive of cocaine availability. Overall, these results demonstrate that pregabalin may have potential in the treatment of some aspects of cocaine addiction.